Strict sequential catheter ablation strategy targeting the pulmonary veins and superior vena cava for persistent atrial fibrillation. Issue 2 (August 2018) - Yoshiga, Yasuhiro; Shimizu, Akihiko; Ueyama, Takeshi; Ono, Makoto; Fukuda, Masakazu; Fumimoto, Tomoko; Ishiguchi, Hironori; Omuro, Takuya; Kobayashi, Shigeki; Yano, Masafumi
Highlights: The pulmonary vein isolation (PVI) alone strategy was sufficient to suppress persistent atrial fibrillation (AF) in 66% of persistent AF patients. Superior vena cava isolation (SVCI) suppressed persistent AF in some patients with persistent AF resistant to PVI. A sequential PVI and SVCI suppressed persistent AF in 74% of persistent AF patients. Persistent AF duration predicted the persistent AF recurrence after sequential PVI and SVCI. Abstract: Background: An effective catheter ablation strategy, beyond pulmonary vein isolation (PVI), for persistent atrial fibrillation (AF) is necessary. Pulmonary vein (PV)-reconduction also causes recurrent atrial tachyarrhythmias. The effect of the PVI and additional effect of a superior vena cava (SVC) isolation (SVCI) was strictly evaluated. Methods: Seventy consecutive patients with persistent AF who underwent a strict sequential ablation strategy targeting the PVs and SVC were included in this study. The initial ablation strategy was a circumferential PVI. A segmental SVCI was only applied as a repeat procedure when patients demonstrated no PV-reconduction. Results: After the initial procedure, persistent AF was suppressed in 39 of 70 (55.7%) patients during a median follow-up of 32 months. After multiple procedures, persistent AF was suppressed in 46 (65.7%) and 52 (74.3%) patients after receiving the PVI alone and PVI plus SVCI strategies, respectively. In 6 of 15 (40.0%) patients with persistent AF resistant to PVI, persistent AF was suppressed. The persistent AF duration independently predicted persistent AF recurrences after multiple PVI alone procedures [HR: 1.012 (95% confidence interval: 1.006–1.018); p < 0.001] and PVI plus SVCI strategies [HR: 1.018 (95% confidence interval: 1.011–1.025); p < 0.001]. A receiver-operating-characteristic analysis for recurrent persistent AF indicated an optimal cut-off value of 20 and 32 months for the persistent AF duration using the PVI alone and PVI plus SVCI strategies, respectively. Conclusions: The outcomes of the PVI plus SVCI strategy were favorable for patients with shorter persistent AF durations. The initial SVCI had the additional effect of maintaining sinus rhythm in some patients with persistent AF resistant to PVI.